Survey of medication history of patients with stroke after discharge from an acute hospital ward: a case series study - Yuko Fukuda; Risa Ito; Misaki Kakihana; Tsutomu Takahashi; Tetsuji Kanemoto; Toshiyuki Sahara; Masahiko Tsujikawa; Mitsuko Onda (Journal of Pharmaceutical Health Care and Sciences)
Abstract Background Stroke is a leading cause of death, reducing disability-free life expectancy. After acute treatment, patients require rehabilitation to prevent recurrence. Continued use of medication is crucial for recurrence prevention and risk management, even after the transition from acute-care institutions to other medical institutions. Although “discharge summaries on medications” are shared between hospitals and community pharmacists, no reports have addressed medication continuity for patients with stroke transferred to other institutions after discharge. This study aimed to clarify medication continuity, particularly for medications adjusted during hospitalization that should be continued even after discharge, by investigating the medication use histories of patients with stroke transferred from acute care hospitals to outpatient hospitals. Methods We enrolled patients who were discharged from an acute ward between June 11, 2022, and March 31, 2023, after receiving inpatient care at the Japan Community Healthcare Organization, Hoshigaoka Medical Center for acute stroke, and transferred to other outpatient hospitals. This study was conducted between June 2022 and April 2023. We extracted and assessed prescription continuity and carefully examined clinically relevant discrepancies after comparing the discharge prescription with that at the first outpatient visit. Results Of the 42 patients enrolled, seven (16.7%) had one or more discrepancies involving 13 medications. Based on the medicinal efficacy classification, four patients treated with other blood and body fluids-related agents (antiplatelet drugs), three patients treated with agents for hyperlipidemia (statins), two patients with agents for peptic ulcers, two patients with vasodilators, one patient treated with antihypertensives, and one patient with other agents affecting digestive organs (antiemetic agents that acts on the central nervous system) had discrepancies. Furthermore, discrepancies in medication discontinuation or reduction recommended by a stroke specialist, which may increase the risk of stroke recurrence, were identified in five patients (seven drugs: four antiplatelet drugs and three statins). Of 13 discrepancies, community pharmacists inquired about 3 cases with physicians, none were approved. Conclusion The medication to prevent stroke recurrence might not be continued after transit to another outpatient after discharge. Reconsidering patient information sharing between hospital and community pharmacists and establishing a more strengthened sharing system is necessary to achieve seamless pharmacotherapy.